New Mycomya species from the Himalayas (Diptera, Mycetophilidae): 2. Subgenera Calomycomya, Cymomya, Neomycomya and Pavomya subg. n. - Väisänen, Rauno (Zootaxa, 2013)
Mycomya Rondani specimens from the Himalayas, mostly Nepal and Myanmar, are revised. Pavomya subg. n. is de-scribed. Altogether nine species from the subgenera Calomycomya, Cymomya, Neomycomya and Pavomya subg. n. are recorded from the Himalayas and Indian subcontinent. The paper includes a key to the subgenera of Mycomya and the Himalayan species of Mycomya of the four subgenera. The following eight new species are described: M. aonyx, M. cuon, M. kambaitiensis, M. marmota, M. paguma, M. panthera, M. ratufa and M. wah. Mycomya fimbriata (Meigen) is recorded from Myanmar.